The utility of apparent diffusion coefficient in diagnosis of acute cholecystitis - Musafir Atea Hashim (Medical Journal of Babylon, 2018)
Background: Acute cholecystitis (AC) is a very common gastrointestinal pathology. Patient's history, physical examination, and laboratory investigations are usually not sufficient for accurate diagnosis. Moreover, imaging findings can overlap with that of many other gallbladder pathology especially chronic cholecystitis (CC). Therefore, there is a reasonable necessity for new diagnostic tools for AC. Objective: This study aimed to evaluate the efficiency of the apparent diffusion coefficient (ADC) as a diagnostic tool for AC and differentiating it from CC. Materials and Methods: During the period from April 2017 to March 2018, a total of 62 patients with suspected cholecystitis were enrolled in this prospective cross-sectional study. Patients were subjected to diffusion-weighted imaging, from which the ADC values were calculated. All patients were then undergone laparoscopic or open cholecystectomy, and the diagnosis of AC or CC was proven through histopathological examination. Receiver operating characteristic analysis was used to find out the area under the curve (AUC), sensitivity, and specificity of ADC in the diagnosis of AC. Results: The average value of ADC from three regions of interests from patients with AC was 1.434 ± 0.31 × 10−3 mm2/s. On the other hand, the average ADC from CC was 2.032 ± 0.31 × 10-3 mm2/s with significant difference (P = 0.013). The AUC was 0.803, 95% confidence interval = 0.702–0.905, P < 0.001, with a sensitivity and a specificity of the test at 1.94 × 10−3 mm2/s cutoff value were 0.70 and 0.73, respectively. Conclusions: These results indicate a good diagnostic value of ADC in discrimination between acute and CC. Further studies using contrast media are required for more accurate evaluation of ADC as a diagnostic tool for AC.